Introduction to the taxonomy of Iulomorphidae of New Zealand, with descriptions of two new species of Eumastigonus Chamberlin, 1920 (Diplopoda: Spirostreptida: Epinannolenidea) - Korsós, Zoltán; Johns, Peter M. (Zootaxa, 2009)
The single New Zealand genus, Eumastigonus Chamberlin, 1920, of the millipede family Iulomorphidae (Spirostreptida: Epinannolenidea) is reviewed, diagnosed, and its morphological characters are discussed. Redescription of the generotype E. kaorinus Chamberlin, 1920, further records of E. distinctior Chamberlin, 1920, and E. hemmingseni Mauriès, 1983, and descriptions of two new species: E. hallelujah sp. n. and E. waitahae sp. n. are given.